Effect of Geraniol on Brain Cholesterol, Vitamin A and E Levels in The Hydrogen Peroxide-Treated Rats - Şahin, Zafer; Özkaya, Ahmet; Ökkeş,; Yılmaz, Okkes; Yilmaz,; Görgülü, Ahmet Orhan (My University, 2018)
Aim: Geraniol, a monoterpene, is a plant-derived natural antioxidant. Hydrogen peroxide ($H_2O_2$) is amember of reactive oxygen species (ROS). The objective of this study is to de-termine the effect ofgeraniol on brain cholesterol and lipophilic vitamins such as vitamin A (retinol) and vitamin E (alpha (?)-tocopherol and ?-tocopherol acetate) in $H_2O_2$ -administrated male rats.Materials and Methods: Adult male Wistar rats were randomly divided into four groups (n=7). Geraniol(50 mg/kg) and $H_2O_2$ (16 mg/kg) were administered by an intraperitoneal injection for 30 days with a1-day interval. Brain samples were homogenized and cholesterol, ?-tocopherol, ?-tocopherol acetate, andretinol levels analyzed from lipid extracts by HPLC.Results: Brain cholesterol level was found to be significantly higher in the $H_2O_2$ group than the controlgroup. Brain ?-tocopherol acetate levels were found to be significantly higher in the $H_2O_2$ and thegeraniol+$H_2O_2$ groups than the control group. There was no difference in retinol levels between anygroups.Conclusion: In conclusion, our results indicate that brain cholesterol and ?-tocopherol acetate levels areaffected by $H_2O_2$-induced oxidative stress. Moreover, we suggest that geraniol has the potential to reducethe effect of $H_2O_2$ in male rats.
Keywords: Biyoloji; Kimya; Tıbbi